(untitled) (Revista Latino-Americana de Enfermagem, 2000)
The Program of Community Integration of the Municipal Bureau of Health of the city of Ribeirão Preto aims at promoting health, directing its actions for the change of life styles. The purpose of this study is to look, in the light of the framework of Health Promotion and through declarations of users of the program, how it has been formed as an important strategy to increase the autonomy and emancipation of the population. The analysis reveals that the program has improved the autonomy and emancipation of the population, as an important instrument for life defence.